Announcement of Kurdistan Democratic Party (KDP) 1976-1991 - Muhammed kaka Sur Muhammed; Regr Bahadin Sharif Regr Bahadin Sharif (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The period 1976-1991 is an important period in the history of the Kurdistan Democratic Party (KDP), especially due to the collapse of the September Revolution and the revival of the May Revolution The publications of the Kurdistan Democratic Party (KDP) can be relied upon as a historical source for researching the historical events of that period. This research consists of a gate and three topics. In the door, we have focused on the media institution that has been in the media department of the Political Bureau of the Kurdistan Democratic Party (KDP) since 1979. He has seen PKK newspapers and publications, and has published several books and pamphlets. The second topic is about the Intelligence Department. At this stage, Insat has had a special importance for monitoring the local and international media. We have discussed this department and its work in detail. The third topic is about the archives and library of the PKK and its work, the importance of the department and the people who worked in this department, we have presented.